Mining in Obuasi: Conflict, Social Justice and Peace-Building (1890-2014) - Amoah, E. B. (University of Ghana, 2022)
The Obuasi mining communities had functioned for two centuries without engaging in violent conflict, in contrast to another region of Africa where gold mining had led to colonialist land politics with informal and unembedded social mechanisms for resolving conflicts. Although they equally face similar and worse developmental deficits that have led some African countries into civil war. In several mining societies in Africa, mineral set-ups are threatened by structural violence caused by unemployment, exclusion, poverty, discrimination, disrespect for local beliefs, and marginalization, among others. These intangible variables are moral principles and values that are mostly ignored in the legal and plural justice systems in mining communities. The often-frosty relationship between local communities and foreign companies has always resulted in ecological, socio-economic, and political conflicts. As a result, in the post-colonial era, indigenous peoples or mining communities lack confidence in their government or mining corporations on a number of concerns, such as their security, socio-economic rights, and ecological rights, among other things. Therefore, peace-building mechanisms become essential to ensure human survival through a social contract. The main goal of this study was to investigate the mining negotiation strategies that AngloGold Ghana Limited and the Obuasi community used from 1890 to 2014 to guarantee peaceful coexistence. This study critically examines the social-legal history of mining in Obuasi by teasing out and discussing issues of human rights and peace-building mechanisms during the period under study. The study largely uses archival materials, oral history, oral interviews, and focus group discussions for the analysis and interpretation of issues. The study uses local peace-building approaches as a conceptual tool to examine the peace-building processes in the Obuasi mining community. The study argues that the nature of peace experienced in Obuasi mining communities during the period was a result of the various land and mining ordinances, communitarian living, manipulative justice, and the role of spiritual vigilantes, which have resulted in the current illegal mining phenomenon in the community. Indigenous formal structures embedded in duabɔ, Ntam, dwantoa, Akyɔwpa (apology), landscape Features, mitigating factor for long-term peace, “proverbs’, and “strategic silence” were in the pre colonial and colonial periods, as well as the foundation for efficient and effective peace-building systems in Obuasi. It was also discovered that the post-colonial peace-building system, which used national security architecture and plural legal structures, was effective at intimidating host communities into proving justice and fundamental human rights violations caused by mining activities. The study also observed the threat to livelihood and social security from the excessive manipulation of justice by the colonists using the formal structures of chieftaincy and democratic governance. Mining security was also threatened after the mining company started surface mining in the early 1990s, which rendered the host communities in structural poverty since their land for farming is now used for mining. Even during election seasons, the gap between the community's livelihood challenges and the financiers of the political party inciting the youth to engage in illegal mining operations that destroy their own water bodies , air and forests resource poses a significant threat to human existence.
PhD. African Studies
Keywords: Obuasi; mining communities; Africa